INTEGRATION OF SPIRITUAL GUIDANCE PROGRAM IN LEARNING TO DEVELOP THE CHARACTER OF MILLENNIAL STUDENTS - Iqnaa, Faiq; Hina, Shahzadi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the integration of the Spiritual Guidance Program in learning at the Nurul Jadid Islamic Boarding School ,and its impact on the character formation of millennial students. The main focus of this research is to understand how spiritual guidance, which is based on Islamic spiritual values and ethics, can be applied in learning to foster stronger character among students. The research method used is a qualitative approach with a case study type, which involves observation, in-depth interviews with key informants such as Islamic boarding school mudirs, curriculum leaders, Sufism teachers, and Islamic boarding school students, and analysis of existing program documentation . The research results show that integrating spiritual guidance in learning helps develop students' character and increases their spiritual awareness, which is very important in facing the challenges of the millennial era. Apart from that, characteristics such as discipline, responsibility, and concern for others are increasingly formed through applying this guidance. The implications of this research show that spiritually based programs need to be strengthened in Islamic boarding school education as a basis for producing students who have strong, ethical characters and are ready to adapt to an increasingly modern world. Keywords: Spiritual Guidance, Santri Character, Islamic Boarding School Education